SPIRITUALITY AND RELIGION AS AN AGENT OF RECOVERY IN PATIENTS WITH DEPRESSION AND ANXIETY - Andromahi Naumovska; Dimitar Bonevski (Medicinska naklada, 2019)
Spirituality has been found to be an important component in the recovery of severe mental illness. During the past two decades, researches has connected spirituality to a variety of benefits, including increased hope, well-being, self-esteem, social supports, motivation towards growth, as well as decreased depression, anxiety, and substance abuse. Studies show that religion and spirituality are associated with decreased rates of mental illness, but the association between religion, spirituality and mental illness are still understudied. So this study of 31 patients with depression and 31 patients with anxiety disorders, have examined the influence of the support of the spiritual guide and the support of the psychotherapist. The study design used semi-structured open-ended interview about who attended or not a ‘spirituality guide’ together with psychotherapy and their individual subjective feelings of mental wellness through that social support. Data shows that those who reported use of spiritual guide and psychotherapy generally have more positive individual’s subjective feelings of mental wellness. Accessing a spiritual support together with psychotherapy may be useful within mental health recovery from the view point of those in receipt of it. Spirituality can be viewed as a vital dimension of holistic practice and person-centered care, as a form of stress reduction, and mindfulness cognitive therapy. The clinicians who are aware of the common themes among the faith and religious believes and can understand the patient's belief system are better prepared to address more appropriate, in crisis situations.